This Is How I Remember: The Beaches of Agns, Documentary Narration, and Building a Self in Film. Issue 2 (1st September 2019) - Jacobs, Matthew
The Beaches of Agns (Les plages dAgns, Varda, 2008) could be described as a film essay, a memoir, an autobiography, or categorized as a documentary; while each of these may be accurate, the film pushes at the edges of these terms, playing with ideas of truth, fictionality and methods of re-creation. There is a constant tension in the film between La Varda the legendary French New Wave filmmaker, Agns Varda the human director, and Agns Varda the subject of investigation. From a narrative theory standpoint, there is a constant tension between the Narrated-I (the Varda being investigated as a historical subject) and the Narrating-I (some combination of the Varda we see on-screen and the implied Varda-author). The documentary nature of the film, documentary being heavily dependent on ideas of authority, recreation, and facticity, is a concern for Varda as she plays with these conventions in her own recreations and playful fictionalizing. These efforts and effects all lead to an amount of purposeful distancing between the real Varda, the on-screen Varda, and the Varda in recreation. This distancing mirrors the construction of the author implied author narrator system: the author Varda (actually visible, perhaps, glimpsed in the acts of directing); the implied Varda-author (present in the final decisions we see in camerawork, framing, and story progression) (the implied author here also, curiously, is the subject of the film); and the character-narrator, the Varda who takes the viewer through the film. These complications of self and past provide an opportunity to examine the films narrative construction, in which different aspects of the same self are presented simultaneously but are being put to different purposes. These techniques are part of Agns Vardas larger desire to destabilize the center subject of the film and to mediate that destabilization in the films construction. Varda mirrors in the films construction the techniques shes using to outline the image of herself as the films subject: using techniques of fictionality and conventions of narrative to build an assemblage film and assemblage subject. Varda produces an impression of her subject, an outline built as decentered assemblage, giving a portrait of herself in a new type of modest (Bonner 121) autobiography-documentary.